2012
DOI: 10.1093/ckj/sfs086
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of a previously transplanted kidney: does success come with a price?

Abstract: Longer wait times for deceased donor kidney transplant have prompted newer initiatives to expedite the process. Reuse of a previously transplanted kidney might be appropriate in certain circumstances. However, one must also consider the unique issues that may arise after such transplants. We describe our experience in one such case where the donor kidney had lesions of focal and segmental glomerulosclerosis and signs of alloreactivity (positive C4d staining) prior to transplantation and the recipient developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…The most common cause of the loss of a kidney allograft is the death of a patient with a functioning graft [11, 15, 16]. In the 30 years since Al-Hasani et al first reported the reuse of a transplanted kidney [4], there have been only 10 case reports of the reuse of a kidney [413].…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of the loss of a kidney allograft is the death of a patient with a functioning graft [11, 15, 16]. In the 30 years since Al-Hasani et al first reported the reuse of a transplanted kidney [4], there have been only 10 case reports of the reuse of a kidney [413].…”
Section: Discussionmentioning
confidence: 99%
“…Donation of organs from recipients late after initial transplantation carries risks of transmission of multidrug-resistant organisms or organisms that typically occur later post transplant (eg, Cryptococcus, Nocardia), as demonstrated in a report of a suspected transmission from an organ recipient of ganciclovir-resistant CMV through kidney transplantation. 4 Our report has several limitations. First, we were unable to identify HSV-2 in the initial organ donor's clinical samples.…”
Section: Discussionmentioning
confidence: 79%
“…Our report illustrates that particular care must be taken to ensure that an infectious complication did not contribute to the potential donor's death. Donation of organs from recipients late after initial transplantation carries risks of transmission of multidrug‐resistant organisms or organisms that typically occur later post transplant (eg, Cryptococcus , Nocardia ), as demonstrated in a report of a suspected transmission from an organ recipient of ganciclovir‐resistant CMV through kidney transplantation …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations